Analisis Keanekaragaman Jenis Plankton di Perairan Pulau Semujur dan Muara Sungai Kurau Kabupaten Bangka Tengah - Damara, Danu; Utami, Eva; Hudatwi, Mu’alimah (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2022)
Plankton is small organisms that live floating in the water column and are very important components in aquatic ecosystems. The purpose of this study was to determine the type of plankton, the ecological index of plankton, and the relationship between the. Physico-chemical parameters of the waters on the diversity of plankton species using statistical analysis. This research was conducted in March-April 2021 on Semujur Island, Pangkalan Baru District and Muara Sungai Kurau. Plankton data collection was carried out vertically using a plankton net. The results showed that the types of plankton found in the waters of Semujur Island and the Estuary of the Kurau River, Central Bangka Regency were 45 types of plankton. The highest plankton diversity value was at station III, namely 2.603 and the lowest value was at station VI, namely 1.361. The highest uniformity index is at station IV at 0.939 and the lowest value is at station V, which is 0.775. The highest value of the dominance index is at station VI, which is 0.307 and the lowest value is at station IV, which is 0.084. The results of the Spearman correlation in the waters of Semujur Island and the estuary of the Kurau River showed that temperature, pH, salinity, and current velocity were positively correlated and in the same direction as plankton diversity. Meanwhile DO and brightness was negatively correlated and opposite in direction to plankton diversity